Applied Linguistics in Public Relations: Bibliometric and Thematic Trends in an Evolving Research Field - Muam, Ahmad; Lugman, Erizal; Binti Ishak, Nurhamizah (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to map and interpret the intellectual structure, thematic evolution, and research trends at the intersection of applied linguistics and public relations over the past decade. The primary objective is to identify key authors, influential sources, dominant themes, and methodological shifts that characterize this emerging interdisciplinary field. Bibliometric data were retrieved from the Scopus database, covering peer-reviewed journal articles published between 2016 and 2025 that explicitly address both applied linguistics and public relations. Using Biblioshiny (Bibliometrix) for performance indicators, collaboration networks, thematic maps, and keyword co-occurrence, and NVivo 12 for qualitative content analysis, this study integrates quantitative and qualitative approaches to provide a comprehensive understanding of the field’s evolution. The results reveal a significant increase in publication output and thematic diversification, indicating rapid intellectual growth. Five dominant thematic clusters were identified: AI and Natural Language Processing (NLP), Digital and Social Media Communication, Health Communication, Discourse and Organizational Communication, and Cross-Cultural Communication. A strong methodological shift toward computational linguistics, big data analytics, and sentiment analysis is evident, accompanied by growing attention to ethics, transparency, and trust in digital public discourse. Emerging frontiers include AI-driven communication modeling, crisis discourse in digital media, multilingual brand communication, and ethnolinguistic perspectives on organizational trust.